Initiating or Switching to Insulin Degludec/Insulin Aspart in Adults With Type 2 Diabetes in the Philippines: Results from a Prospective, Non-interventional, Real-World Study - Nicodemus Jr., Nemencio; Ang-Golangco, Nerissa; Aquitania, Grace; Ardeña, Gregory Joseph Ryan; Dampil, Oliver Allan; Fernando, Richard Elwyn; Flor, Nicole-Therese; Kho, Sjoberg; Matawaran, Bien; Mirasol, Roberto; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Objectives. Blood glucose levels of the majority of Filipino patients with type 2 diabetes (T2D) remain uncontrolled. Insulin degludec/insulin aspart (IDegAsp) is a fixed‑ratio co-formulation of the long‑acting basal insulin degludec and the rapid-acting prandial insulin aspart. The real-world ARISE (A Ryzodeg® Initiation and Switch Effectiveness) study investigated clinical outcomes across six countries in people with T2D who initiated IDegAsp. This publication presents the clinical outcomes of the Filipino cohort from a subgroup analysis of the ARISE study. Methodology. This 26-week, open-label, non-interventional study examined outcomes in adults with T2D initiating or switching to IDegAsp (N=185) from other antidiabetic treatments per local clinical guidance. Results. Compared with baseline, there was a significant improvement in glycated hemoglobin at the end of study (EOS) (estimated difference [ED] −1.4% [95% confidence interval −1.7, −1.1]; P <0.0001). Fasting plasma glucose (ED −46.1 mg/dL [−58.2, −34.0]; P <0.0001) and body weight (ED −1.0 kg [−2.0, −0.1]; P = 0.028) were significantly reduced at EOS compared with baseline. IDegAsp was associated with a decrease in the incidence of self-reported healthcare resource utilization. Adverse events were reported in eight (4.3%) participants. Conclusions. Initiating or switching to IDegAsp was associated with improved glycemic control, lower body weight, and lower HRU for people with T2D in the Philippines. No new, unexpected AEs were reported.